Sewage treatment effluents in Delhi: A key contributor of β-lactam resistant bacteria and genes to the environment. (December 2017) - Lamba, Manisha; Ahammad, Shaikh Ziauddin
Abstract: Rapid emergence of antibiotic resistance (AR) in developing countries is posing a greater health risk and increasing the global disease burden. Lack of access to safe drinking water, poor sanitation and inadequate sewage treatment facilities in these countries are fueling the problem associated with emergence of AR. Rapid proliferation of AR mediated by treated and untreated discharges from sewage treatment plants (STPs) is a prime public health concern. This study aims to understand the occurrence, fate, and routes of proliferation of carbapenem (KPC) and extended spectrum β-lactam (ESBL) resistant bacteria, and selected resistant genes in the samples collected from different unit operations in 12 STPs in New Delhi over two seasons. Strong correlation observed between faecal coliform levels and KPC (R = 0.95, p = 0.005, n = 60) and ESBL (R = 0.94, p = 0.004, n = 60) resistant bacteria levels indicates possible association of resistant bacteria with faecal matter. Different unit operations in STPs proved inefficient in treating resistant bacteria and genes present in the wastewater. However, inclusion of tertiary treatment (chlorination) unit and anaerobic digester in the present STPs resulted in better removal of AR. Significant correlations between antibiotic resistant genes (ARGs) and integron levels indicates a potential for higher rate of AR proliferation in the environment. Microbial culturing indicated the presence of clinically significant drug-resistant pathogens such as Escherichia coli, Pseudomonas putida, Pseudomonas aeruginosa, Enterobacter cloacae, Klebsiella pneumoniae, Klebsiella oxytoca, Acinetobacter baumannii, Shigella dysentery and Aeromonas caviae in the STP effluents. The emergence and spread of resistant bacteria through STP effluents poses exposure risk for the residents of the city. Graphical abstract: Highlights: Presence of high levels of antibiotic resistance (ARB and ARGs) in STP effluents in New Delhi. Significant correlations between ARB and FC as well as ARGs and integron genes were observed. High abundance of carbapenem resistant Escherichia coli and Pseudomonas aeruginosa in the STP effluents. STP having chlorination unit and anaerobic digester performed better in treating ARB and ARGs.